2021
DOI: 10.1167/jov.21.8.22
|View full text |Cite
|
Sign up to set email alerts
|

Close - but not distant - conditioned flanker emotion affects crowding

Abstract: Crowding is affected by conditioned stimulus emotion. This effect is clearly observed for conditioned flankers, but only marginally pronounced for conditioned targets. Studies on the processing of emotional stimuli suggest that the magnitude of the emotional effect depends on the presentation depth in that effects of emotion increase with decreasing distance to the observer in depth. Based on respective findings, we investigate crowding with stimuli of conditioned negative and neutral emotion across real depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, four studies have investigated the effect of depth on crowding using a real depth display. All four studies used two orthogonally positioned screens viewed through a half-transparent mirror allowing stimuli to be displayed on two different depth planes simultaneously ( Eberhardt et al, 2021 ; Eberhardt and Huckauf, 2019 ; Eberhardt and Huckauf, 2017 ; Eberhardt and Huckauf, 2020 ). Eberhardt and Huckauf, 2017 kept a target and flankers at the same depth and presented them 0.06 diopters (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, four studies have investigated the effect of depth on crowding using a real depth display. All four studies used two orthogonally positioned screens viewed through a half-transparent mirror allowing stimuli to be displayed on two different depth planes simultaneously ( Eberhardt et al, 2021 ; Eberhardt and Huckauf, 2019 ; Eberhardt and Huckauf, 2017 ; Eberhardt and Huckauf, 2020 ). Eberhardt and Huckauf, 2017 kept a target and flankers at the same depth and presented them 0.06 diopters (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, four studies have investigated the effect of depth on crowding using a real depth display. All four studies used two orthogonally positioned screens viewed through a half-transparent mirror allowing stimuli to be displayed on two different depth planes simultaneously (Eberhardt et al, 2021; Eberhardt and Huckauf, 2019, 2017, 2020). Eberhardt and Huckauf (2017) kept a target and flankers at the same depth and presented them 0.06 diopters in front, behind or at the same depth as fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, learning can be specific for the target and the flankers. Eberhardt, Pittino, and Huckauf (2021) investigated how the presentation depth of target and flankers modulated the emotional conditioning effect where performance deteriorates when flanker features are negatively conditioned. They presented target and flankers in different (real) depth planes, and found that negatively conditioned flankers (but not targets) yielded worse performance than neutrally conditioned flankers when the flankers were presented closer than or at fixation depth, suggesting that emotional conditioning of stimulus parts does not only depend on whether they are targets or flankers but also at what relative position they are presented.…”
mentioning
confidence: 99%